Top K Nearest Book Searching Approach in Metaverse Libraries Based on R-Tree - Wu, Yubing; Lin, Yifeng; Yang, Yuer; Xu, Wei (2023 International Conference on Networks, Communications and Intelligent Computing (NCIC), 2023)
With the rapid development of network information technology, more and more researchers focus on the construction of metaverse libraries. What remains a challenge is how to find the nearest books in the metaverse libraries accurately and effectively. This paper proposes a top k nearest book searching approach in metaverse libraries based on R-tree. We compare the proposed searching algorithm based on R-tree with the baseline linear scanning in a 2D graph. The state-of-the-art searching algorithm based on grids is also compared. Experimental results demonstrate that our proposed searching algorithms based on R-tree outperform linear scanning and the best searching algorithm based on grids by being approximately 99.940% faster and approximately 90.998% faster respectively. Furthermore, the proposed approach, the searching algorithm based on R-tree, can be extended to find the top k nearest points of q (x, y, z) in 3D spaces in metaverse libraries if the bookshelves are designed to be 3D ones.